Determinan Perilaku Kepatuhan Minum Obat pada Pasien Hipertensi Usia Produktif di Pelayanan Kesehatan Primer: Scoping Review - Kusniawati Kusniawati; Herawati Herawati; Didik Dwi Sanyoto; Oski Illiandri; Syamsul Arifin (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Hypertension is a major global health problem and a leading risk factor for cardiovascular disease. Although effective antihypertensive medications are widely available, poor medication adherence remains a significant challenge in achieving optimal blood pressure control, particularly among productive-age patients. Objective: This scoping review aimed to identify and synthesize evidence on the determinants of medication adherence among productive-age hypertensive patients (aged 18–59 years) in primary care settings. Methods: The review followed the Joanna Briggs Institute (JBI) framework and the PRISMA Extension for Scoping Reviews (PRISMA-ScR) guidelines. A comprehensive literature search was conducted in PubMed, Scopus, ScienceDirect, and Google Scholar for articles published between 2016 and 2026. Studies involving productive-age participants (18–59 years) that examined determinants of adherence to antihypertensive medication were included. Results: A total of 14 studies met the inclusion criteria. The findings revealed that medication adherence among productive-age hypertensive patients was influenced by multiple factors, including sociodemographic characteristics (age, education, economic status), self-efficacy, health literacy, treatment-related factors (regimen complexity, side effects), healthcare system support (effective communication, counseling), social support, and digital health interventions (mobile applications, electronic reminders). Conclusion: Medication adherence among productive-age hypertensive patients is a multidimensional behavior. Comprehensive, integrated strategies are required, including patient education, enhancing self-efficacy and health literacy, simplifying treatment regimens, strengthening communication with healthcare providers, and using technology-based interventions to improve long-term adherence and blood pressure control.